2010
DOI: 10.1093/ntr/ntq030
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of smoking cessation among adult smokers in Malaysia and Thailand: Findings from the International Tobacco Control Southeast Asia Survey

Abstract: Introduction: Limited longitudinal studies on smoking cessation have been reported in Asia, and it remains unclear whether determinants of quitting are similar to those found in Western countries. This study examined prospective predictors of smoking cessation among adult smokers in Thailand and Malaysia.Methods: Four thousand and four smokers were surveyed in Malaysia and Thailand in 2005. Of these, 2,426 smokers were followed up in 2006 (61% retention). Baseline measures of sociodemographics, dependence, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
89
8
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 34 publications
(48 reference statements)
27
89
8
1
Order By: Relevance
“…Our study did not find age, gender or urban/rural residence to be a significant predictor which is similar to the findings from the four country ITC survey (Hyland, et al, 2006) of western countries in year 2006 but different from the recent ITC study from Malaysia and Thailand in 2010 which reported both age and urban/ rural residence to be a significant predictors of quit attempts (Lin et al, 2010). It has also investigated some unique factors like type of family structure, community (caste), rural versus urban residence, which have strong socio-cultural influence in rural areas which were not found to be associated in the present case but may certainly be worth studying further by qualitative methods in any future comprehensive assessment.…”
Section: Discussioncontrasting
confidence: 80%
“…Our study did not find age, gender or urban/rural residence to be a significant predictor which is similar to the findings from the four country ITC survey (Hyland, et al, 2006) of western countries in year 2006 but different from the recent ITC study from Malaysia and Thailand in 2010 which reported both age and urban/ rural residence to be a significant predictors of quit attempts (Lin et al, 2010). It has also investigated some unique factors like type of family structure, community (caste), rural versus urban residence, which have strong socio-cultural influence in rural areas which were not found to be associated in the present case but may certainly be worth studying further by qualitative methods in any future comprehensive assessment.…”
Section: Discussioncontrasting
confidence: 80%
“…The negative association between the number of cigarettes smoked per day and quit attempts that we found is consistent with studies conducted among the general population of smokers in China, Thailand, and Malaysia (Li et al, 2010;Yang et al, 2011). Another study conducted in China did not find this association but found that the time to first cigarette, another measure of cigarette dependence, predicted quit attempts .…”
Section: Discussionsupporting
confidence: 91%
“…In many studies of predictors, 15,22 results for gender, number of previous attempts, education level and social status, years of smoking, and history of depression have been inconsistent. In our study, a more comprehensive list of potential predictors from five domains (namely, demographics, health-related, smoking-related, psychosocial, and interventional variables) was included.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 The link between self-efficacy and successful quitting has long been established. 22,38 Both external and internal self-efficacy in SEQ-12 scales have been found to be predictive in smoking cessation in western countries. 21 In our study, after adjusting all potential predictors, a high degree of confidence and external self-efficacy were predictive of cessation, while the predictive ability of total and internal sub-score of SEQ-12 faded after adjustment.…”
Section: Discussionmentioning
confidence: 99%